Linking of Transformational Leadership, Learning Culture , Organizational Structure and School Innovation Capacity : CB SEM AMOS Analysis - Agus Purwanto; Khaerul Fahmi; Anwar Sulaiman (AGUSPATI RESEARCH INSTITUTA, 2023)
- This study aims to measure the influence of transformational leadership, learning culture and organizational structure on the innovation capacity of schools. Data collection was carried out using simple random sampling via electronics on a population of elementary school teachers. The population in this study are private school teachers whose number is not known with certainty. Questionnaires were distributed electronically using simple random sampling technique. This research method is a quantitative survey. The data collection technique in this study used an online questionnaire technique which was designed using a Likert scale of 1 to 7 and distributed to 650 teachers selected by the simple random sampling method. This data processing tool uses Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structure) version 26. Before conducting data analysis, the validity and reliability of the questionnaire used was tested first. To measure its validity, the score of each question item is used which is correlated with the total item score in one variable. After testing the validity and reliability, then performed data analysis. Analysis and interpretation of data is carried out to answer the problems that have been formulated and answer the hypotheses. In this study, data analysis used Structural Equation Modeling (SEM) with AMOS software. The results of this study are that transformational leadership has a significant effect on learning culture, transformational leadership has a significant effect on organizational structure. Learning culture has a significant effect on innovation capacity. Organizational structure has a significant effect on innovation capacity. The learning culture has a significant effect on the capacity for innovation.